Postinfectious Acute Cerebellar Ataxia in Childhood - (:unkn) unknown (DERMAN MEDICAL PUBL, 2016)
Aim: Postinfectious acute cerebellar ataxia is the most common cause of childhood ataxia. Cases present with acute onset of ataxia to pediatric emergency and pediatric neurology clinics. Varicella zoster is the most commonly associated virus. The aim of this study is to assess the clinical features, etiology, and prognosis of children with postinfectious acute cerebellar ataxia and to propose a diagnostic approach to acute cerebellar ataxia in children. Material and Method: Files of 16 children admitted between January 2011 and June 2015 were retrospectively evaluated. Results: Nine patients were male (56.2%). The majority of the cases were in the 2-5 years age group (62.5%). A history of a preceding febrile infection was noted in 87.5% of the cases: Two children had varicella infection, one Epstein Barr infection, and the rest nonspecific febrile illness. The mean time interval between the prodromal febrile illness and the onset of the symptoms was 7.4 (+/- 5) days. The mean time of hospitalization was 4.37 (+/- 1.4) days. The median time for recovery was 7 days. The longest time for recovery was 4 months. Discussion: Postinfectious acute cerebellar ataxia in childhood is the most common cause of childhood ataxia, which presents abruptly and requires recovery over weeks. However, it should be kept in mind that it is a diagnosis of exclusion. Appropriate utilization of laboratory tests and imaging studies is necessary for the differential diagnosis from other serious causes of acute cerebellar ataxia including central nervous system infections and mass lesions. KeywordsPostinfectious
Keywords: Postinfectious Acute Cerebellar Ataxia; Children; Cerebellitis; Varicella Infection; Cerebellar Ataxia; OPSOCLONUS-MYOCLONUS; CHILDREN; NEUROBLASTOMA; PROGNOSIS